1980
DOI: 10.1111/j.1476-5381.1980.tb10884.x
|View full text |Cite
|
Sign up to set email alerts
|

BEHAVIOURAL CHANGES INDUCED BY N,N‐DIMETHYLTRYPTAMINE IN RODENTS

Abstract: I N,N-Dimethyltryptamine (DMT) in pargyline pretreated rodents induced a dose-dependent behavioural syndrome consisting of hyperactivity, prostration and hindlimb abduction, mild tremor, Straub tail, retropulsion and jerking. 2 In rats pretreated with pargyline, the behavioural syndrome induced by DMT differed from that induced by L-tryptophan or quipazine, in the lack of forepaw treading and head-weaving and in the presence of only mild tremor. 3 The hyperactivity component of the DMT-induced behavioural synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…On the basis of these findings, which were discovered before sigma receptor identification, DMT has been hypothesized to act through an unknown “hallucinogen” receptor (8). We confirmed results (28) that intraperitoneal (ip) administration of DMT (2 mg per kilogram of body weight) 2 hours after pargyline (75 mg/kg, ip) injection induced hypermobility in WT mice (7025 ± 524.1 cm, n = 12 WT mice) in an open-field assay. Identical drug treatments in sigma-1 receptor KO mice had no hypermobility action (2328 ± 322.9 cm, n = 12 KO mice, P < 0.0001; Fig.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…On the basis of these findings, which were discovered before sigma receptor identification, DMT has been hypothesized to act through an unknown “hallucinogen” receptor (8). We confirmed results (28) that intraperitoneal (ip) administration of DMT (2 mg per kilogram of body weight) 2 hours after pargyline (75 mg/kg, ip) injection induced hypermobility in WT mice (7025 ± 524.1 cm, n = 12 WT mice) in an open-field assay. Identical drug treatments in sigma-1 receptor KO mice had no hypermobility action (2328 ± 322.9 cm, n = 12 KO mice, P < 0.0001; Fig.…”
supporting
confidence: 89%
“…DMT injection induces hypermobility in rodents concurrently treated with the monoamine oxidase inhibitor pargyline (28), and this action is not antagonized by blockers of dopamine or serotonin receptors, but is potently inhibited by haloperidol (28). Although haloperidol is thought to act in part through the dopamine D 2 receptor system, it is also a potent sigma-1 receptor agonist [sigma-1 inhibition constant ( K i ) = 3 nM (29); sigma-2 K i = 54 nM (29)] when inhibiting voltage-gated ion channels (5, 25).…”
mentioning
confidence: 99%
“…Some DMT behavior did not involve the 5-HT or other monoaminergic systems (29), and the DMT-enhanced phosphatidylinositol production was not blocked by the 5-HT 2A receptor antagonist ketanserin (30). Therefore, 5-HT receptors are not the sole mediators of DMT psychodysleptic effects.…”
Section: Discussionmentioning
confidence: 92%
“…These findings will be discussed in more detail in the paragraph on cardiovascular effects in section 5. Mild cross-tolerance to DMT was reported in humans made tolerant to LSD (Rosenberg et al, 1964; Jenner et al, 1980). Taken together, these findings suggest that tolerance can develop to the cardiovascular and other peripheral effects of DMT, although little or no tolerance develops to the subjective effects.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Although the serotonin system has been thought to be the main contributor to the psychedelic effects of DMT, other behavioral effects have been observed which do not involve the serotonin or other monoaminergic systems; such as jerking, retropulsion, and tremors (Deliganis et al, 1991; Jenner et al, 1980). In addition, molecular effects of DMT have been identified that are not mediated by serotonin receptors.…”
Section: Introductionmentioning
confidence: 99%